Can electricity market prices control power-to-heat production for peak shaving of renewable power generation? The case of Sweden. (1st June 2019) - Åberg, Magnus; Lingfors, David; Olauson, Jon; Widén, Joakim
Abstract: 100% renewable energy systems require high penetration of variable renewable electricity (VRE) generation. This causes the net load in the system to be more variable and could cause operational problems in local power grids. Demand side management (DSM), such as fuel or energy carrier switching in response to a price signal, can provide flexibility to meet the increased variability. This study investigates the impact of VRE production on electricity prices and their potential to act as an incentive to control district heating power-to-heat (P2H) production in order to shave VRE production peaks. Also, the potential to increase P2H production flexibility with additional heat storages is studied. Electricity prices are simulated by modification of historical electricity market supply curves. A heat storage component is implemented in an existing model for district heat production. The results show that P2H production is significantly increased (up to 98%) when electricity prices are influenced by VRE production. Thermal storages further increase the P2H production by up to 46%. The increased P2H production, however, does not necessarily coincide with the peaks of VRE. Thus, in conclusion, the pricing mechanism on the Nord pool electricity market is insufficient to control P2H production for shaving VRE production peaks. Highlights: Large amounts of VRE reduce mean and peak electricity prices. VRE-influenced electricity prices can increase P2H production by 98%. The Nord pool electricity price is insufficient for shaving VRE peaks with P2H. The potential to increase P2H production with heat storages is limited.